2022
DOI: 10.21203/rs.3.rs-1446898/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sedation is associated with higher polyp and adenoma detection rates during colonoscopy: a retrospective cohort study

Abstract: Background and aims: Currently sedation is a common practice in colonoscopy to reduce pain of patients and improve the operator satisfaction, while its impact on examination quality, especially polyp detection rate (PDR) and adenoma detection rate (ADR) is still controversial. Thus, we aimed to investigate the association of sedation with PDR/ADR. Methods: Consecutive patients receiving colonoscopy between January 2017 to January 2020 at the Nanjing Drum Tower Hospital were collected. Univariate and multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Our results revealed that after adjusting potential confounding factors, the colonoscopy with sedation was significantly associated with higher ADR. After PSM, the results were still stable, which indicated that sedation was an independent factor associated with a higher ADR [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that after adjusting potential confounding factors, the colonoscopy with sedation was significantly associated with higher ADR. After PSM, the results were still stable, which indicated that sedation was an independent factor associated with a higher ADR [ 22 ].…”
Section: Discussionmentioning
confidence: 99%